PSYCHOLOGICAL AND PEDAGOGICAL FOUNDATIONS OF THE ORGANIZATION ORIENTED EDUCATION - Sayyora Turaxodjayevna Shermetova (European Science Publishing, 2024)
The article discusses the system of intellectual and practical skills abilities of students, a learning model based on a scientific psychological and pedagogical concept.
Keywords: research work, subjective experience, creative activity, teaching and research skills, didactic process, emotional-volitional attitude.